2015
DOI: 10.1021/acs.nanolett.5b02402
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization Dynamics of Organolead Halide Perovskite by Real-Time X-ray Diffraction

Abstract: We analyzed the crystallization process of the CH3NH3PbI3 perovskite by observing real-time X-ray diffraction immediately after combining a PbI2 thin film with a CH3NH3I solution. A detailed analysis of the transformation kinetics demonstrated the fractal diffusion of the CH3NH3I solution into the PbI2 film. Moreover, the perovskite crystal was found to be initially oriented based on the PbI2 crystal orientation but to gradually transition to a random orientation. The fluctuating characteristics of the crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
87
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(102 citation statements)
references
References 26 publications
10
87
0
Order By: Relevance
“…[161] Sawicka et al claimed that methyl ammonium halides decompose into methyl halides and neutral amines take places at 600 K. [162] The realization of a hybrid perovskite from a lead dihalide and an organic halide is anticipated to release 0.1 eV per unit cell, [163] so close to the site of active perovskite creation there may be sufficient free energy to decompose some MAI into NH 3 and CH 3 I. Since MAI intercalates the lead dihalide prior to establishing the perovskite phase, [164] it is relatively feasible that if MAI decomposition happens, it will occur within either the PbCl 2 or PbI 2 precursor that the products, especially the CH 3 I, might be trapped in the final perovskite structure.…”
Section: Thermally Induced Chemical Decompositionmentioning
confidence: 99%
“…[161] Sawicka et al claimed that methyl ammonium halides decompose into methyl halides and neutral amines take places at 600 K. [162] The realization of a hybrid perovskite from a lead dihalide and an organic halide is anticipated to release 0.1 eV per unit cell, [163] so close to the site of active perovskite creation there may be sufficient free energy to decompose some MAI into NH 3 and CH 3 I. Since MAI intercalates the lead dihalide prior to establishing the perovskite phase, [164] it is relatively feasible that if MAI decomposition happens, it will occur within either the PbCl 2 or PbI 2 precursor that the products, especially the CH 3 I, might be trapped in the final perovskite structure.…”
Section: Thermally Induced Chemical Decompositionmentioning
confidence: 99%
“…[37] This phenomenon was reported in several other publications dealing with different fabrication methods. [37,[56][57][58][59] In their study, Oesinghaus et al further suggested that the presence of Cl -promotes the dissolution of the PbI 2 layer, leading to more crystals oriented in (002) direction (cf. Figure 2f).…”
Section: Two-step (Sequential Deposition)mentioning
confidence: 98%
“…[45] The in-situ conversion mechanism can explain why MAPI crystals are frequently observed to be tilted by an angle χ = 55° when produced via 2-step deposition. [14,34,42,48,49] Thus, simply by tuning the porosity of the PbI 2 layer, e.g., by variation of the spin-coating temperature, it is possible to tune the crystal orientation of MAPI films (cf. Figure 3b-d).…”
Section: Research Newsmentioning
confidence: 99%
“…e,f) Reproduced with permission. [48] Copyright 2015, American Chemical Society. g) Exemplary 2D GIWAXS images where reflexes from individual grains were tracked during film annealing to monitor grain rotation.…”
Section: Research Newsmentioning
confidence: 99%